2015
DOI: 10.1111/apt.13309
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus in patients with decompensated chronic liver disease: a prospective UK/French study

Abstract: SUMMARY BackgroundIn developed countries, hepatitis E is a porcine zoonosis caused by hepatitis E virus (HEV) genotype 3. In developing countries, hepatitis E is mainly caused by genotype 1, and causes increased mortality in patients with preexisting chronic liver disease (CLD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 50 publications
2
73
0
2
Order By: Relevance
“…A UK/French study also looked at the role of HEV infection in patients with decompensated chronic liver disease. 66 Acute HEV infection (genotype 3) was identified in a minority (3.2%) of patients with decompensated chronic liver disease, and there were no differences in mortality between patients with and without HEV infection.…”
Section: Clinical Featuresmentioning
confidence: 91%
See 2 more Smart Citations
“…A UK/French study also looked at the role of HEV infection in patients with decompensated chronic liver disease. 66 Acute HEV infection (genotype 3) was identified in a minority (3.2%) of patients with decompensated chronic liver disease, and there were no differences in mortality between patients with and without HEV infection.…”
Section: Clinical Featuresmentioning
confidence: 91%
“…65 Autochthonous (locally acquired) HEV infection is not a benign condition, with mortality rates up to 27% reported in patients with underlying chronic liver disease ( Figure 1). 66 Interesting geographical variations in genotype 3 HEV infection have been observed in France where there is considerable variation in seroprevalence by region from 8-86% 67 ; very high seroprevalence occurs in the southwest, southeast and northeast of the country. [66][67][68] The reason for this interesting observation is unclear, but contaminated foodstuffs in the food chain are likely to explain these geographical differences in part.…”
Section: Genotypementioning
confidence: 99%
See 1 more Smart Citation
“…One Indian study found that 28% of cirrhotic patients were HEV-RNA positive, with a 12-month mortality rate of 70% in this group versus 30% in non-infected individuals [31] . In developed countries, hepatitis E is an uncommon cause of decompensation, but varies by geographical location (1.1% in the UK; 7.9% in southwestern France [32] ). The mortality rate in these areas is not significantly different between patients with HEV-related decompensation and those with other causes (27 vs. 26%) [32] .…”
Section: Acute Infectionmentioning
confidence: 99%
“…In developed countries, hepatitis E is an uncommon cause of decompensation, but varies by geographical location (1.1% in the UK; 7.9% in southwestern France [32] ). The mortality rate in these areas is not significantly different between patients with HEV-related decompensation and those with other causes (27 vs. 26%) [32] . This possibly reflects differences in the pathogenicity of the dominant genotypes in different regions (HEV1 and HEV3 respectively) [33] .…”
Section: Acute Infectionmentioning
confidence: 99%